La flora medicinal andina en las preparaciones tradicionales de la comunidad de Ocumazo (Pueblo Omaguaca), Jujuy, Argentina - Tortoni, Gisella Ludmila (2021)
Introduction: Traditional knowledge about medicinal plants is part of the health system of indigenous communities. The use of multiple combined species is frequent in the Argentine Northwest, but studies focused on the subject are scarce. This study describes and contextualizes the uses of these preparations.M&M: We applied participant observation techniques in the indigenous community of Ocumazo, Humahuaca, Jujuy, Argentina, with its prior informed consent. Open interviews were undertaken with key collaborators and other adults, through sampling by networks and by opportunity. We investigated the elaboration of recipes and how people used them. Further, we analyzed the administration and the context of application. The data were analyzed with qualitative techniques. Results: 12 combinations of 26 plant species were surveyed (69% native, 23% cultivated, 9% adventitious), including animal products. In daily life, medicinal preparations are used for respiratory, gastrointestinal, bone, and musculoskeletal diseases, among others. In the context of ritual celebration, the beverages take on symbolic significance.Conclusions: The inhabitants of Ocumazo articulate precise knowledge about the ways to combine the species and to administrate the formulas. In a ritual context, the selection of species and the elaboration of recipes differ from daily use. The community has its own knowledge about the distribution of species according to warm or cold qualities prevailing notions of Hippocratic humoral medicine.